Pacific FL15 and Golfo FL 16: two (2) high-yielding and long-grained rice varieties available for seeds production and commercialization in Mexico - CGIAR Research Program on Rice (2019)
Basic seed was produced by INIFAP in October 2016 and delivered to the Mexican Rice Council in 2017. The first lot of certified seed of both varieties was 300,000 tons